Democratization and research methods - Coppedge, Michael, 1957- (Cambridge ; New York : Cambridge University Press, 2012)
"Democratization and Research Methods is a coherent survey and criti que of both democratization research and the methodology of comparative politics. The two themes enhance each other: the democratization liter ature illustrates the advantages and disadvantages of various methodolo gical approaches, and the critique of methods makes sense of the vast a nd bewildering democratization field. Michael Coppedge argues that each of the three main approaches in comparative politics - case studies an d comparative histories, formal modeling and large-sample statistical a nalysis - accomplishes one fundamental research goal relatively well: ' thickness', integration and generalization, respectively. Throughout th e book, comprehensive surveys of democratization research demonstrate t hat each approach accomplishes one of these goals well but the other tw o poorly. Chapters cover conceptualization and measurement, case studie s and comparative histories, formal models and theories, political cult ure and survey research, and quantitative testing. The final chapter su mmarizes the state of knowledge about democratization and lays out an a genda for multi-method research"--
1. Research methods and democratization; 2. Defining and measuring d emocracy; 3. Criteria for evaluating causal theories; 4. Checklists, fr ameworks, and Boolean analysis; 5. Case studies and comparative history ; 6. Formal models and theories; 7. Rigor in extensive and intensive te sting; 8. Political culture and survey research; 9. Quantitative testin g; 10. An agenda for future research.
Includes bibliographical references and index.
Keywords: Democratization -- research -- Methodology; Comparative government -- Research -- Methodology